The Analysis Of Overall Equipment Effectiveness On The Heading Machine To Minimize Six Big Losses Using The Total Productive Maintenance Method: A Case Study Of PT XYZ - Reza Ade Irmansyah; Widya Setiafindari (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2026)
Abstract Machine efficiency and productivity are key factors in the manufacturing industry to ensure product quality and smooth production processes. PT XYZ, as a company engaged in manufacturing, faces challenges in optimizing the performance of its Heading machine used during the production process. One of the identified problems is the high downtime, which averages 5,509.7 minutes per month during the research period. This study applies the Overall Equipment Effectiveness (OEE) and Six Big Losses methods to analyze machine effectiveness and designs improvement recommendations through the Total Productive Maintenance (TPM) approach. Data collected over a six-month period, from January to June 2024, shows that the Heading machine has an availability rate of 86.63%, a performance rate of 87.93%, and a quality rate of 99.55%, resulting in a total OEE value of 75.5%. The Six Big Losses analysis indicates that the main factor affecting machine effectiveness is reduced speed losses. Therefore, this study recommends the implementation of TPM to improve the effectiveness of the Heading machine performance at PT XYZ.